Pengaruh Tingkat Indikator Worry terhadap Self-Regulated Learning Siswa Sekolah Dasar dalam Menyelesaikan Soal Cerita Matematika - Redi Gunawan; Elly Susanti; Abdussakir (AB-JME: Al-Bahjah Journal of Mathematics Education, 2026)
Cognitive anxiety in the form of worry can interfere with students' ability to regulate the learning process, especially when solving mathematical word problems. This study aims to analyze the effect of worry levels on fifth-grade elementary school students' Self-Regulated Learning (SRL) in solving mathematical word problems. This study used a quantitative approach with a causal associative design. The research sample consisted of 38 fifth-grade elementary school students in one of the elementary schools in Cirebon selected through a purposive sampling technique. Data were collected using a four-point Likert scale questionnaire to measure three indicators of worry, namely self-doubt, fear of failure, and cognitive interference, as well as three phases of SRL, namely forethought, performance control, and self-reflection. In addition, students' answer sheets were analyzed descriptively based on Polya's problem-solving stages. The results showed that worry had a negative and significant effect on students' SRL with a value of B = -0.898, r = -0.710, p <0.001, and R² = 0.504. This means that the higher the student's worry, the lower their self-regulation ability, with a contribution of 50.4%. Students with high levels of worry experienced a decline in SRL, particularly during the forethought and self-reflection phases, as evidenced by difficulties planning solutions, incomplete work steps, and a lack of rechecking of answers. These findings underscore the importance of teacher support in reducing worry and strengthening students' SRL at each stage of solving math word problems.